2009
DOI: 10.1038/ijo.2009.228
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expressions of circadian-clock and circadian clock-controlled genes in the livers and kidneys of long-term, high-fat-diet-treated mice

Abstract: Objectives: Physiological and behavioral circadian rhythmicities are exhibited by all mammals and are generated by intracellular levels of circadian oscillators, which are composed of transcriptional/translational feedback loops involving a set of circadianclock genes, such as Clock, Per1-3, Cry1-2, Bmal1, Dbp, E4BP4 and CK1e. These circadian-clock genes play important roles in regulating circadian rhythms and also energy homeostasis and metabolism. Determining whether obesity induced by high-fat diet affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 59 publications
(79 reference statements)
3
79
0
Order By: Relevance
“…It was reported that transcripts of Bmal1 and Clock in the liver increased from the end of the dark phase to the beginning of the light phase in mice with a 12-h light/12-h dark cycle and ad libitum feeding (from ZT21 to ZT3). Conversely, transcripts of Per1-3 were increased from the end of the light phase to the beginning of the dark phase (from ZT6 to ZT18) [28,29].…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that transcripts of Bmal1 and Clock in the liver increased from the end of the dark phase to the beginning of the light phase in mice with a 12-h light/12-h dark cycle and ad libitum feeding (from ZT21 to ZT3). Conversely, transcripts of Per1-3 were increased from the end of the light phase to the beginning of the dark phase (from ZT6 to ZT18) [28,29].…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, only a few studies have investigated the relationship existing between different diets and circadian clock regulation in wild-type mice. The effect of administering high-fat diet on the expression of clock genes has so far been studied in different tissues (Kohsaka et al 2007;Barnea et al 2009;Hsieh et al 2010;Yanagihara et al 2006), but to date, alterations of clock gene expression in the gut following administration of high-fat diet in wild-type mice have never been reported.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Furthermore, the circadian-clock genes, Bmal1, Clock, Per1-3, and Cry1-2, control the circadian rhythm of physiological output by regulating the expression of multiple downstream circadian-clock-controlled genes, including Dbp (albumin D-site-binding protein) and E4BP4 (basic leucine zipper transcription factor) (Gekakis et al, 1998). In addition to the central circadian pacemaker, the hypothalamic suprachiasmatic nucleus, circadian-clock genes are also expressed in many peripheral tissues, including the heart, lung, kidney, and liver (Hsieh et al, 2010;Oishi et al, 1998;Shieh, 2003;Shieh et al, 2005), but the physiological role of these genes in peripheral tissues is not fully understood.…”
Section: Introductionmentioning
confidence: 99%